WSN and IoT based smart city model using the MQTT protocol. (17th November 2019) - Kumar, Vishal; Sakya, Gayatri; Shankar, Chandra
Abstract: The Internet of things in integration with wireless sensor networks changed the world exponentially by connecting a huge number of devices and providing the ability to control them remotely and globally. This research work is emphasized on proposing the smart city model and implementation that model based on IoT using MQTT protocol. The comparison is done with HTTP protocol. HTTP is used for transferring the information using request and response model so require control packets overhead. To handle the limitation of HTTP, MQTT is proposed. It uses publish/subscribe model, reduces control packets overhead and suitable for IoT. It uses "Named based routing" and prevents IP address in IoT data transfer. The smart city model is proposed and developed using Network Simulation Software (Cisco Packet Tracer v7.2).Cisco introduces IoT and MQTT feature in version 7.1. Here Message Queuing Telemetry Transport (MQTT) protocol is used which gives fast and reliable performance for IoT devices. A network model is developed with multiple sensors and IoT Devices which acts as MQTT client. Here a data center is created which has multiple Servers (MQTT Broker). Using the MQTT broker all the IoT devices can be monitored by just logging in to the broker. A prototype model is implemented and tested in real time using Node MCU. The devices are remotely monitored from anywhere in the world which fulfill the requirement of smart city model. Future aspects include the integration of machine learning algorithms in the protocols developed for IoT for quick smart decisions in monitoring the critical applications.